Clinical and mechanical factors associated with the removal of temporary epicardial pacemaker wires after cardiac surgery - Elmistekawy, Elsayed; Gee, Yen-Yen; Une, Dai; Lemay, Matthieu; Stolarik, Anne; Rubens, Fraser D (Université d'Ottawa | University of Ottawa, 2016)
Abstract Background Temporary pacemaker wires are placed in the majority of patients after cardiac surgery. There is no information on mechanical factors related to wire removal. Methods Clinical information related to temporary wire use and removal was prospectively collected from a large cardiac surgical unit over one year. Measurements of maximal tension that nurses and doctors would apply to remove temporary wires was determined using a hand-held portable scale. In a prospective trial, patients (n = 41) had their wires extracted in series to the portable scale to determine the maximal tension required for safe removal. Results Ventricular wires were placed in 86.5 % of patients during the observed year. Pacing facilitated weaning from CPB in over 15 % of patients and pacer dependence was seen in 2.1 %. No patients suffered major complications after wire removal. There was no difference in the tension that physicians or nurses would apply to comfortably extract temporary wires. In the prospective trial, there was no difference in the tension required for removal of atrial or ventricular wires (atrial 18.3 ± 17.9 oz versus 14.5 ± 14.2 oz, p = 0.430). There were no patient factors that correlated with the degree of resistance and there was no significant difference between the tension required to remove wires with (21.0 ± 22.5 oz) or without (14.1 ± 5.1 oz) an atrial button. Conclusions Temporary epicardial wire removal is innocuous and was not associated with any complications. In some patients tension required for safe removal exceeded 20 ounces. Strategies to standardize wire removal may prevent complications and may minimize unnecessary wire retention.